Procollagen-Lysine, 2-Oxoglutarate 5-Dioxygenase Family: Novel Prognostic Biomarkers and Tumor Microenvironment Regulators for Lower-Grade Glioma - Gong, Siming; Wu, Changwu; Köhler, Franziska; Meixensberger, Jürgen; Schopow, Nikolas; Kallendrusch, Sonja (Frontiers in Cellular Neuroscience, 2022)
Lower Grade Glioma (LGG) are a group of tumors arising from cells of the central nervous system. Although various therapy interventions are used, the prognosis remains variable. Novel biomarkers are needed for prognosis of disease and for novel therapeutic strategies in LGG. The Procollagen-Lysine, 2-Oxoglutarate 5-Dioxygenase (PLOD) family contains three members and is related to multiple cancers, yet it was not investigated in LGG. Data from the Chinese Glioma Genome Atlas (CGGA) and The Cancer Genome Atlas (TCGA) cohort were used to analyze the role of PLOD in LGG. As the PLOD family is involved in processes such as tumor formation and cancer metastasis, we focused on its relation to the tumor microenvironment (TME) in LGG. A high expression of the PLOD family relates to poor prognosis and high infiltration of immune cells within the TME. The expression level of the PLOD family might become a novel biomarker for prognosis and is a potential target for individual treatment decisions in LGG.